The Ambivalence of Accounting Education Among University Students: Towards a Collaborative Learning Environment - Sithole, Nosihle Veronica; Dube, Bekithemba (Research in Social Sciences and Technology- OpenED Network, 2025)
This empirical paper proposed collaborative learning as a strategy to enhance performance in Accounting among university students. There has been a notable continuous trend of poor performance in Accounting from the first-year level to the fourth year. Again, there is also a noticeable decline in the number of students majoring in Accounting despite alternatives to enhance Accounting among university students. This paper is underpinned by bricolage theory which advocates the reworking the existing ideas or items to produce something new to improve human conditions. We responded to two questions: what is the cause of poor performance in Accounting among university students and how collaborative learning can be utilised to mitigate poor performance in Accounting among university students? Data was collected through semi-structured interviews with three students and three lecturers who were purposively sampled. Thematic analysis was used to analyse the data collected. Findings revealed that lack of content conceptualisation, students’ negative attitudes towards Accounting, lack of academic commitment, and lack of Accounting pedagogical skills are the main reasons for poor performance among university students. Further, findings revealed that collaborative learning in Accounting among university students broadens students’ content knowledge and produces students with a variety of skills. In light of the above findings, we argued that collaborative learning should premise the teaching and learning of Accounting in higher education from a bricolage perspective.